Chickpea is a promising agricultural crop - S. K. Shchukis; E. R. Shchukis (Зерновое хозяйство России)
Chickpea is a promising agricultural crop It’s necessary to introduce high protein crops in the sowings to strengthen food and forage security of Russia and the Altay Area. The main advantage of chickpea as a high protein crop among all leguminous crops is its high drought tolerance. The kernels contain 19-30% protein, 4-7% oil, 48-56% nitrogen-free extractives, zinc, folic acid and on 89-97% digested. Chickpea is one of the oldest cultivated crops, it’s widely spread throughout the world and it’s third among the legumes after soybean and beans. In Russia, its sowings are widely distributed in the Caucasus and the Povolzhie. In the Altai, a wide ecological trials of chickpeas occurred in the 80s of the last century. The crop gave good results in the steppe regions, where it surpassed productivity of the zoned varieties of peas in almost 1.5 times. Since 2017 a new variety of chickpea ‘Kulundinsky 5’ has been introduced into the State List of the Breeding Achievements approved to use in the West-Siberian region (approval 23.01.2017, №9001 from 03.03.2017). The variety has been developed by the FSBSI FARCA using the method of mass selection of one-type lines from heterogeneous population with the participation of the varieties ‘Krasnokutsky 28’, ‘Uzbekistansky 32’ and ‘Maksad’. The variety is Trans-Caucasus carneum, the variety of average-ripening type with 90-100 days of vegetation. The variety shows the similar resistance to lodging, cracking of beans and shedding of seeds as the standard variety. Drought resistance is high. Resistance to diseases and pests is similar to the standard variety ‘Privo 1’. Considering chickpea as a valuable source of vegetable protein, it should improve the set of cultivated crops in the arid regions not only of the Altai Area, but also of the West Siberian region. At the same time, it is obvious that its productivity is not stable through the years. The disadvantages of the crop include a tendency to grow in cool wet years, and its infection with ascochitis and fusariosis.